2016
DOI: 10.1021/jacs.6b01663
|View full text |Cite
|
Sign up to set email alerts
|

Highly Stable Zr(IV)-Based Metal–Organic Frameworks for the Detection and Removal of Antibiotics and Organic Explosives in Water

Abstract: Antibiotics and organic explosives are among the main organic pollutants in wastewater; their detection and removal are quite important but challenging. As a new class of porous materials, metal-organic frameworks (MOFs) are considered as a promising platform for the sensing and adsorption applications. In this work, guided by a topological design approach, two stable isostructural Zr(IV)-based MOFs, Zr6O4(OH)8(H2O)4(CTTA)8/3 (BUT-12, H3CTTA = 5'-(4-carboxyphenyl)-2',4',6'-trimethyl-[1,1':3',1″-terphenyl]-4,4″… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
795
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 1,359 publications
(809 citation statements)
references
References 81 publications
14
795
0
Order By: Relevance
“…For systems with carboxylate ligands containing hard oxo donors, hard Lewis acids, that is, metal cations with high-charge density, which are typically represented by tetravalent zirconium, have been intensively studied for the construction of stable MOFs610. Although debates on the hydrolytic stability of some zirconium based MOFs remain1112, examples exhibiting decent stabilities under extremely acidic conditions (for example, concentrated HCl solutions) have been shown13141516. However, there has been lacking a single example of MOF compound that can survive all fuming acids including nitric acid, aqua regia and oleum solutions that are often required for a variety of chemical processes such as used nuclear fuel reprocessing (for example, 8 M HNO 3 ).…”
mentioning
confidence: 99%
“…For systems with carboxylate ligands containing hard oxo donors, hard Lewis acids, that is, metal cations with high-charge density, which are typically represented by tetravalent zirconium, have been intensively studied for the construction of stable MOFs610. Although debates on the hydrolytic stability of some zirconium based MOFs remain1112, examples exhibiting decent stabilities under extremely acidic conditions (for example, concentrated HCl solutions) have been shown13141516. However, there has been lacking a single example of MOF compound that can survive all fuming acids including nitric acid, aqua regia and oleum solutions that are often required for a variety of chemical processes such as used nuclear fuel reprocessing (for example, 8 M HNO 3 ).…”
mentioning
confidence: 99%
“…The rational design metal-organic coordination polymers (CPs) have received remarkable attention, not only because of their fascinating architectures and topologies but also because of their potential applications as functional materials [3][4][5][6][7][8]. It is well known that topologies of coordination polymers have a significant impact on their physical and chemical properties [9][10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…In 2016, Wang et al reported two isostructural Zr-MOFs, Beijing University of Technology (BUT)-12 and BUT-13 ( Figure 15). 34 Both MOFs demonstrate their stability in boiling water for 7 days, concentrated HCl for 24 h, and NaOH solution (pH = 10) for 24 h. It is purposed that the presence of methyl groups on the central phenyl ring of the organic linker increases the hydrophobic character of the frameworks and therefore raises their water stability. 29 By examining the contact angle of water with the material, the extent of hydrophobicity of the framework and thus water stability can be anticipated.…”
Section: Hydrophobic Groupsmentioning
confidence: 99%
“…At low pressures, the water uptakes of the MOFs are 18.5% and 15.1% of the total water uptakes for BUT-12 and BUT-13, respectively. 34 This suggests strong hydrophobicity on the surface of these materials and is likely to act as a contributing factor for their water stability. In addition to synthesizing MOFs with ligands that have methyl groups inherently, alkyl groups can also be introduced into MOFs via postsynthetic modification.…”
Section: Hydrophobic Groupsmentioning
confidence: 99%